RANCANG BANGUN DAN OPTIMASI INSTRUMEN LASER DIODA INAKTIVASI (LDI) UNTUK TERAPI PENYAKIT PERIODONTAL (PENELITIAN SECARA IN VITRO) - I GDE BAGUS YATNA WIBAWA, 091425053004 (2017)
The aim of this study is to determine the potential of the laser diode 445 nm and 650 nm with a extract chlorophyll of Moringa oleifera leaf as photosensitizer to inactivate Aggregatibacter actinomycetemcomitans (A.a.) bacteria in photodynamic inactivation (PDI). Laser diodes is used as a source of monochromatic light which harmless with low output power and can be adjusted by controlling the input voltage. Statistical test results showed the control group with 20% extract chlorophyll photosensitizer does not show different results with a control group without the photosensitizer. So it can be concluded that the photosensitizer is not toxic for the A.a. bacteria. This study used multimode optical fiber 8 mm to guide the laser diode beam. The laser diode 445 nm can generate 9.2 mW, 23.3 mW, 37.5 mW, and 51 mW output power, while the laser diode 650 nm can generate 15.3 mW, 25.7 mW, 35 mW, and 45.5 mW output power. Four doses of energy (2,5J.cm-2, 5J.cm-2, 7,5J.cm-2, and 10J.cm-2) are used for both laser diodes in the in vitro photodynamic inactivation test . The test showed that there are more deaths of A.a. bacteria in treatment group with photosensitizer than group without photosensitizer. The highest percentage of deaths occurred in the group treated with the photosensitizer and exposed to laser diode 650 nm with 10J.cm-2 energy dose, which is 83%.